Haralick's texture analysis to predict cellular proliferation on randomly oriented electrospun nanomaterials. Issue 5 (16th February 2022) - Bloise, Nora; Fassina, Lorenzo; Focarete, Maria Letizia; Lotti, Nadia; Visai, Livia
Abstract : Haralick's texture analysis of the biomaterials was used to assess and predict the cell behaviour on a nanomaterial surface. Abstract : Using a computer vision approach we have extracted the Haralick's texture features of randomly oriented electrospun nanomaterials in order to predict the proliferative behavior of cells which were subsequently seeded onto the nanosurfaces.